Analisis Politik Kewargaan Pada Komunitas Transpuan Warna Sriwijaya Di Kota Palembang - Syirin, Fathimah; Viana, Ryllian Chandra Eka; Mirza, Ibrahim Mifthafariz (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the practices of citizenship politics among the Warna Sriwijaya transpuan community in Palembang City within conditions of social and structural constraints. Although transpuan are administratively recognized as citizens, they continue to face social stigma, discrimination, and the absence of legal recognition of gender identity. This study aims to analyze forms of citizenship political practices, the fulfillment of rights, and the political participation of the transpuan community at the local level. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Data analysis is conducted using Kristian Stokke’s framework of citizenship politics, combined with Nancy Fraser’s concept of social justice. The findings indicate that the Warna Sriwijaya transpuan community has exercised citizenship politics through voting rights, political engagement, and interactions with local government. Access to administrative and health services is relatively available; however, the right to decent work remains limited due to an employment system that is not yet inclusive. Overall, the fulfillment of transpuan citizenship rights remains partial.